Approaches to Using the Chameleon: Robust, Automated, Fast-Plunge cryoEM Specimen Preparation - Levitz, Talya S.; Weckener, Miriam; Fong, Ivan; Naismith, James H.; Drennan, Catherine L.; Brignole, Edward J.; Clare, Daniel K.; Darrow, Michele C. (Frontiers in Molecular Biosciences, 2022)
The specimen preparation process is a key determinant in the success of any cryo electron microscopy (cryoEM) structural study and until recently, had remained largely unchanged from the initial designs of Jacques Dubochet and colleagues in the 1980s. The process has transformed structural biology, but it is manual and can require extensive optimisation for each protein sample. The chameleon instrument with its self-wicking grids, and fast-plunge freezing represents a shift towards a robust, automated, and highly controllable future for specimen preparation. However, these new technologies require new workflows and an understanding of their limitations and strengths. As early adopters of the chameleon technology, we report on our experiences and lessons learned through case studies. We use these to make recommendations for the benefit of future users of the chameleon system and the field of cryoEM specimen preparation generally.